Guias Didáticos: Propostas Inovadoras - Lima, Camila Fernandes de; Gomes Junior, Estevão Conceição; Prins, Simone; Camargo Filho, Paulo Sérgio de; Magalhães, Leandro Henrique; Bailoni, Ludmila Fratucci (Livros Editora UniFil; Livros Editora Unifil, 2023)
Acesse o e-book aqui:  https://drive.google.com/file/ d/ 1MIjJ5dNkCjhz3QzbQ3jkGwTL7wlTL -1S/view